2009
DOI: 10.1002/cm.20417
|View full text |Cite
|
Sign up to set email alerts
|

Centriole symmetry: A big tale from small organisms

Abstract: Centrioles are microtubule-based cylindrical organelles with a 9-fold symmetry. They are essential for axoneme formation in cilia and flagella and for centrosome organization. In the basal hexapods Acerentomon microrhinus, we discovered unusually large centrioles composed of 14 doublet microtubules that serve as templates for cilia and flagella and organize mitotic and meiotic spindles. These observations challenge the long-standing view that centriole symmetry is highly conserved among eukaryotes. Strikingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
(26 reference statements)
2
11
0
Order By: Relevance
“…S1B) as demonstrated previously (25). This is similar in size to the central tubules of most of the model organisms (supplemental Table 1) with the exception of the hexapod Acerentomon microrhinus, where the diameter of the central tubule varied according to the centriole diameter (27). Analysis of cryo-EM tomograms of centrosomes suggested that the central tubule is an extended structure along the axis of the centriole (supplemental Movies 1 and 2).…”
Section: Sas-6 Is a Component Of The Centriole Central Tubule-tosupporting
confidence: 81%
“…S1B) as demonstrated previously (25). This is similar in size to the central tubules of most of the model organisms (supplemental Table 1) with the exception of the hexapod Acerentomon microrhinus, where the diameter of the central tubule varied according to the centriole diameter (27). Analysis of cryo-EM tomograms of centrosomes suggested that the central tubule is an extended structure along the axis of the centriole (supplemental Movies 1 and 2).…”
Section: Sas-6 Is a Component Of The Centriole Central Tubule-tosupporting
confidence: 81%
“…The axoneme is the structural backbone of the cilium and mirrors the nine-fold radial symmetry conveyed by the basal body (Riparbelli et al, 2009b). Generally, motile cilia contain a pair of axial singlet microtubules at the center of the axoneme surrounded by the nine doublet microtubules of the axoneme: a “9+2” structure.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism that generates or maintains asymmetry is the regulated trafficking of specific cellular components (Sann et al, 2009;Peters and Kropf, 2010;Poulain and Sobel, 2010). The microtubule cytoskeleton is a key player in intracellular transport and is itself inherently asymmetric as a result of age differences between the two cen trosomes/basal bodies that nucleate the microtubules (Piel et al, 2000;Dutcher, 2003;Anderson and Stearns, 2009;Riparbelli et al, 2009;Wang et al, 2009;Yamashita, 2009) and the inher ent directionality of the tubulin polymer (Li and Gundersen, 2008;Coquelle et al, 2009).…”
Section: Introductionmentioning
confidence: 99%